2013
DOI: 10.1097/dcr.0b013e31826942ee
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Residual Cancer and Lymph Node Metastasis After Noncurative Endoscopic Resection of Early Colorectal Cancer

Abstract: There is a greater need for additional surgery in cases with positive vertical resection margin or inadequate lifting sign, because the risk of residual tumor and lymph node metastasis is higher than in other cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Unlike available series recently published in the literature [6,14,15], lympho-vascular invasion, tumour grade and high-grade budding have only marginally influenced treatment plans.…”
Section: Discussionmentioning
confidence: 72%
“…Unlike available series recently published in the literature [6,14,15], lympho-vascular invasion, tumour grade and high-grade budding have only marginally influenced treatment plans.…”
Section: Discussionmentioning
confidence: 72%
“…Therefore, although lymphovascular invasion can also function as a prognostic predictor of residual disease or recurrence, the scientific evidence is less conclusive. Some authors have shown that lymphovascular invasion is correlated with regional lymph node metastasis and recurrence [5, 8, 23, 27, 28], whereas others have reported no association [2, 7, 18, 29]. Analysis on this matter is further complicated by the fact that lymphovascular invasion is not often seen in endoscopic resection specimens of early colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Positive (<1 mm) or unknown polypectomy margins were associated with residual disease in the colonic wall, and lymphovascular invasion was associated with lymph node metastases. Kim et al [20] published a series of 85 radicalized polypectomy (23.5 % for rectal polyps), showing that positive vertical margin (>pT1sm1) and inadequate lifting sign could be predictors of the presence of residual tumor or lymph node metastases in surgical specimens after non-curative endoscopic resection for early CRC. This study analyzes the role of TEM in the management of MRPs.…”
Section: Discussionmentioning
confidence: 99%